EXPLORING INDONESIAN EFL TEACHERS’ READINESS FOR INTEGRATING ARTIFICIAL INTELLIGENCE IN CLASSROOM PRACTICES - Alifah Dian Fitriah; Erlanda Aprilia; Hanna Amelia Tania; Desi Nahartini; Didin Nuruddin Hidayat (UIN Sumatera Utara, 2025)
The rapid growth of artificial intelligence (AI) in education is a factor introducing significant changes in teaching English as a foreign language (EFL). Many AI-based applications, including chatbots, automated feedback systems, and adaptive platforms, offer the possibility to develop more interactive and personalized learning. Nonetheless, the implementation of AI will be successful if teachers are willing to learn, adapt, and implement it well. The study sought to see the extent to which teachers in Indonesia who teach English are prepared to adopt AI technology in learning activities. The areas studied were teachers' awareness, perceived benefits, difficulties, and flexibility towards AI. The results of this study to provide an initial picture of teachers' willingness to be exposed to digital transformation and can serve as a basis for developing more relevant training and education policies.